FINANCIAL DISTRESS AND TAX MOTIVATION: THE EFFECT ON EARNINGS MANAGEMENT - Reschiwati, Reschiwati; Harwin Hasudungan (Dinasti International Journal of Economics, Finance & Accounting, 2020)
When companies solve financial distress, there are efforts made by companies such as accounting methods, changing accounting estimation, policies, and shifting periods of costs or revenues. Companies also often carry out strategies in dealing with deferred taxes or tax payments, both of which are done is a form of earnings management This study aims to discuss the effect of financial distress and tax motivation on earnings management in transportation service companies approved in the Indonesia Stock Exchange in 2014-2018. Sampling using a purposive sampling technique. From a population of 35 companies, based on the criteria chosen 9 companies were selected as samples. Data processing using panel data regression method. Based on the selection model, the fixed effect is chosen as the analysis model to be used. The results of the study concluded that financial distress determines a significant positive effect on earnings management while tax motivation does not involve earnings management